Association between serum manganese levels and diabetes in Chinese adults with hypertension. Issue 7 (24th June 2022) - Chen, Hong; Cui, Zhixin; Lu, Wenhai; Wang, Ping; Wang, Jia; Zhou, Ziyi; Zhang, Nan; Wang, Zhuo; Lin, Tengfei; Song, Yun; Liu, Lishun; Huang, Xiao; et al.
Abstract: Manganese (Mn) is an essential trace metal element that is associated with diabetes; however, the results of previous studies are inconsistent. Furthermore, few studies have been conducted in a hypertensive population. The purpose of this study is to explore the relationship between manganese and diabetes in a population with hypertension. A cross‐sectional study was conducted, including 2575 hypertensive individuals from 14 provinces in China. Serum manganese concentrations were measured by the inductively coupled plasma mass spectrometry (ICP‐MS) method. And logistic regression models were used to analyze the association between serum manganese and the risk of diabetes. The prevalence of diabetes was 27.0% in this hypertensive population. In logistic regression models, the odds ratios (95% confidence interval) for diabetes in tertile subgroups were 1.40 (1.12, 1.76) and 1.32 (1.05, 1.65) for tertiles 1 and tertiles 3, respectively, compared to tertile 2 (reference). Additionally, an interaction between sex and manganese was observed. The odds ratios (95% confidence interval) for diabetes were 1.29 (0.95, 1.75) and 0.96 (0.70, 1.31) for tertiles 1 and tertiles 3 among males, and 1.44 (1.01, 2.04) and 1.81 (1.29, 2.55) for tertiles 1 and tertiles 3 among females, respectively, compared to tertile 2. In conclusion, a U‐shaped association between serum manganese and diabetes was observed in a Chinese population with hypertension, and the association was modified by sex.